Design and Build a Decision Support System Application to Determine Potential Customers Using the MOORA Method At PT. SUCOFINDO (Persero) Surabaya Main Branch - Dany Prambudi; M. J Dewiyani Sunarto; Agus Dwi Churniawan (Jurnal Sistem Informasi Universitas Dinamika, 2022)
PT. Superintending Company of Indonesia (PERSERO) or known as SUCOFINDO is a company engaged in testing and analysis, audit and inspection, certification, consulting, and training. In order to retain customers from these various sectors, PT. SUCOFINDO (PERSERO) Surabaya Main Branch is committed to giving rewards to selected customers in each period. The selection is done by looking at the total value of the transaction without having a reference or other method used so that it can lead to a subjective assessment of potential customers who will be rewarded by the company. To overcome the existing problems, PT. SUCOFINDO Main Branch Surabaya requires application design in determining potential customers who will receive rewards by using one of the methods used to support decisions, namely Multi-Optimization Objective on The Basis of Ratio Analysis (MOORA). The criteria used in this study consist of the value of customer transactions, frequency of customer transactions, frequency of customer cooperation, and arrears (days). Implementation of a web-based decision support system using the PHP programming language and MySQL as the database. Based on the results of the analysis, system design, and system development that have been carried out, it is found that the functional requirements and calculations carried out both systemically and manually obtained the same calculation results by entering 10 customer transaction data. The system that has been developed produces the largest value with a value of 0.3052 and the lowest value of 0.1613. The selected potential customers are with the largest value, namely 0.3052 in Alternative 8. The existence of a decision support system (SPK) that has been designed and built is expected to assist in the process of assessing and ranking potential customers who will be rewarded during that period.